Treatment of polyimide films by an atmospheric pressure plasma of capacitive RF discharge for liquid crystal alignment - Bazhenov, V.Yu.; Chaplinskiy, R.Yu.; Kravchuk, R.M.; Kuzmichev, A.I.; Piun, V.M.; Tsiolko, V.V.; Yaroshchuk, O.V. (Вопросы атомной науки и техники, 2013)
Uniform planar alignment of liquid crystals is obtained by polyimide films obliquely treated by a stream of argon plasma from capacitive RF discharge at atmospheric pressure. Two liquid crystal alignment modes are discovered differing by their longitudinal or transverse orientation with respect to treatment direction. Optimum parameters of the treatment for obtaining these orientation modes are determined.